BACKGROUND AS METAPHOR AND ATMOSPHERE IN THE NOVEL NORUWEI NO MORI - Salamah, Solechatun; Febrianty, Fenny (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research aims to describe the use of setting as a metaphor and atmosphere and function in the novel Noruwei no Mori by Haruki Murakami. The method used in this research is descriptive analysis with an objective approach to the material objects of the novel Noruwei no Mori by Haruki Murakami. The research results show that the metaphorical setting and atmosphere of death uses elements of music, old buildings, billiard playing areas, and also mental hospital dormitories. The metaphorical setting and atmosphere in this novel give the effect of happiness, anxiety, loss, loneliness, calm and sadness.